2017
DOI: 10.18632/oncotarget.16443
|View full text |Cite
|
Sign up to set email alerts
|

Association of two microRNA polymorphisms miR-27 rs895819 and miR-423 rs6505162 with the risk of cancer

Abstract: Many studies have been conducted to investigate the association between miR-27 rs895819 A > G and miR-423 rs6505162 C > A and cancer risk; however, the results are not consistent. In order to acquire a more precise assessment of the correlation, we performed this meta-analysis. We searched PubMed, EMBASE and Web of Science databases to identify eligible studies. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were applied to evaluate the correlation of these two microRNA polymorphisms with cancer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
(27 reference statements)
1
13
0
Order By: Relevance
“…The protective impact of the C allele on BC development has been confirmed in several case-control studies, including in a Chinese population [C vs. A: OR = 0.628, 95% CI = 0.410-0.961, (Zhang et al, 2013); C vs. A: OR = 0.93, 95% CI = 0.87-0.99 (Zhang et al, 2017b)], German population [C vs. A: OR = 0.88, 95% CI = 0.78-0.99, P = 0.0287 (Yang et al, 2010)], and in all of the populations in a meta-analysis [C vs. A: OR = 0.91, 95% CI = 0.85-0.98, P = 0.02 (Dai et al, 2015)]. SNP rs895819 was also associated with the risk of BC in BRCA2 mutation carriers (Kontorovich et al, 2010), which indicated that this SNP may be involved in familial BC development.…”
Section: Effect Of Rs895819 (A/cmentioning
confidence: 77%
“…The protective impact of the C allele on BC development has been confirmed in several case-control studies, including in a Chinese population [C vs. A: OR = 0.628, 95% CI = 0.410-0.961, (Zhang et al, 2013); C vs. A: OR = 0.93, 95% CI = 0.87-0.99 (Zhang et al, 2017b)], German population [C vs. A: OR = 0.88, 95% CI = 0.78-0.99, P = 0.0287 (Yang et al, 2010)], and in all of the populations in a meta-analysis [C vs. A: OR = 0.91, 95% CI = 0.85-0.98, P = 0.02 (Dai et al, 2015)]. SNP rs895819 was also associated with the risk of BC in BRCA2 mutation carriers (Kontorovich et al, 2010), which indicated that this SNP may be involved in familial BC development.…”
Section: Effect Of Rs895819 (A/cmentioning
confidence: 77%
“…A previous meta-analysis by Chen et al [ 25 ] involving 8 case–control studies with 3697 cases and 5013 controls found that the G-allele at rs895819 was significantly associated with decreased BC risk in the total population. Another recent meta-analysis by Zhang et al [ 26 ] including 9 case–control studies with 4191 cases and 4776 controls found that rs895819 could decrease BC risk according to the allele contrast and dominant models in the total population. In addition, a meta-analysis by Wu et al [ 27 ] including 9 case–control studies with 4499 cases and 5434 controls found that the G-allele at rs895819 is likely associated with decreased BC risk, mainly in Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…miR-27a abnormal expression and mutation has been identified in various malignant tumors, such as breast, renal and colorectal cancer (13,17,18). miR-27a decreased the risk of breast cancer in Caucasians (17) and population with the genetic variant of pre-miR-27a had a lower risk of renal cell carcinoma (RCC) (13). Further, low expressed miR-27a was related to high grade in colorectal cancer (18).…”
Section: Discussionmentioning
confidence: 99%